Forecasting Demand of Moving Average and Linier Regression Methods in Predicting the Production of K93 Disc Brake Product (Case Study of PT United Steel Center Indonesia) - Ersa Salsa Bilaffayza; Wahyudin Wahyudin; Dene Herwanto (Jurnal Rekayasa Sistem & Industri, 2023)
PT United Steel Center Indonesia is a manufacturing company engaged in the steel plate industry. Thecompany produces various kinds of steel plate products and has various plants, one of which is the DiscBrake K93 product. The Disc Brake K93 product is a part request from the largest customer which oftenexperiences significant changes, resulting in fluctuations and causing inventory to accumulate in thewarehouse. Inventories that accumulate can cause losses for the company, due to improper waste accordingto planning, even less inventory can cause losses for the company because it can experience delays indelivery to customers. Forecasting is one method in planning to predict and help draw conclusions.Moving Average and Linier Regression methods are used in this study, and an analysis of the level ofaccuracy is carried out using the concistency of MAD, MSE, and MAPE as well as forecasting validationwith Tracking Signal. Based on the results of processing and analysis, it is found that the linear regressionmethod is the most accurate method in predicting Disc Brake K93 products for the 2022 period with anincrease in production each month, the MAD value is 15242.23, MSE is 371649700, MAPE is 0.201, andthe Tracking Signal is 0.